Determinants of the protective effect of glucocorticoids on mortality in hospitalized patients with COVID-19: Insights from the Cardio-COVID-Italy multicenter study. (July 2021) - Pagnesi, Matteo; Inciardi, Riccardo M.; Lombardi, Carlo M.; Agostoni, Piergiuseppe; Ameri, Pietro; Barbieri, Lucia; Bellasi, Antonio; Camporotondo, Rita; Canale, Claudia; Carubelli, Valentina; Carugo, Stefano; Catagnano, Francesco; et al.
Highlights: Glucocorticoids are an effective therapy for patients hospitalized with COVID-19. The use of glucocorticoids was associated with a lower risk of in-hospital mortality. A protective effect was mainly observed in patients with worse respiratory parameters. Abstract: Background: Glucocorticoid therapy has emerged as an effective therapeutic option in hospitalized patients with coronavirus disease 2019 (COVID-19). This study aimed to focus on the impact of relevant clinical and laboratory factors on the protective effect of glucocorticoids on mortality. Methods: A sub-analysis was performed of the multicenter Cardio-COVID-Italy registry, enrolling consecutive patients with COVID-19 admitted to 13 Italian cardiology units between 01 March 2020 and 09 April 2020. The primary endpoint was in-hospital mortality. Results: A total of 706 COVID-19 patients were included (349 treated with glucocorticoids, 357 not treated with glucocorticoids). After adjustment for relevant covariates, use of glucocorticoids was associated with a lower risk of in-hospital mortality (adjusted HR 0.44; 95% CI 0.26–0.72; p = 0.001). A significant interaction was observed between the protective effect of glucocorticoids on mortality and PaO2 /FiO2 ratio on admission (p = 0.042), oxygen saturation on admission (p = 0.017), and peak CRP (0.023). Such protective effects of glucocorticoids were mainly observed in patients with lower PaO2 /FiO2 ratio (<300), lower oxygen saturation (<90%), and higher CRP (>100 mg/L). Conclusions: The protective effects of glucocorticoids on mortality in COVID-19 were more evident among patients with worse respiratory parameters and higher systemic inflammation.